HCV IRES manipulates the ribosome to promote the switch from translation initiation to elongation - Filbin, Megan E. (2012)
The hepatitis C virus (HCV) internal ribosome entry site (IRES) drives non-canonical initiation of protein synthesis necessary for viral replication. HCV IRES functional studies have focused on 80S ribosome formation, but have not explored roles after the 80S ribosome is poised at the start codon. Here, we report that mutations of an IRES domain that docks in the 40S subunit’s decoding groove and cause only a local perturbation in IRES structure result in conformational changes in the IRES-rabbit 40S subunit complex. Functionally, we find the mutation decreases IRES activity by inhibiting the first ribosome translocation event, and modeling suggests that this effect is through an interaction with a single ribosomal protein. The HCV IRES’ ability to manipulate the ribosome provides insight into how the ribosome’s structure and function can be altered by bound RNAs, including those derived from cellular invaders.